Model Cooperative Learning Pada Pembelajaran Analisis Busana Untuk Meningkatkan Motivasi Dan Hasil Belajar Mahasiswa - Setiawati, As-as (INVOTEC, 2010)
Cooperative Learning Model in Fashion Analysis Study and it’s Role in Increasing Student’sMotivation and Study Result, was conducted using the Classroom Action Research (CAR) approach,going through four cycle in order to solve problem and until the problem is solved. The key incooperative learning is learning to collaborate in a cooperative group. When students study in group, anopen study atmosphere will be created in terms of partnership, because at that very exact moment acollaborative learning process will be born in a symbiotic personal relationship. And at that moment also,peer group and cooperative learning pattern will be developed. To experience happiness and sadness,failure and success together. Having responsible for everyone else in the group, besides the responsibilityfor themselves, in learning faced material. This situation will increase student’s motivation in FashionModel Analysis, particularly fashion pattern scattering.